The Staged Treatment of Diabetic Nephropathy Based on the Principle of “Using Collaterals for General Use” - Zhang, Lijuan; Li, Xiaohui (Journal of Contemporary Medical Practice, 2025)
The basic pathogenesis of diabetic nephropathy collateral disease is the syndrome of deficiency and excess of deficiency and excess of deficiency and excess of deficiency and excess of deficiency and excess of deficiency and excess of deficiency and excess of deficiency and excess of deficiency and deficiency of spleen and kidney, and the obstruction of kidney collateral by water dampness, phlegm and blood stasis and toxin. Therefore, dredging collaterals is the key treatment method. Based on this, this paper proposes the methods of replenishing qi, nourishing Yin and dredging collaterals, activating blood circulation, removing blood stasis and dredging collaterals, promoting water and removing dampness and dredging collaterals, collecting wind and dredging collaterals, nourishing kidney and detoxifying collaterals, warming Yang and dredging collaterals, which provide new ideas and methods for the treatment of diabetic nephropathy.